Avaliação de progênies de Feijão-macuco (Pachyrhizus tuberosus (lam.) Spreng.), Fabaceae, com base na nodulação natural, caracteres associados e processamento de raízes tuberosas - Silva, Edinei Santos da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2015)
The yam bean is a legume that produces edible tuberous roots of considerable nutritional value, with potential for cultivation for large-scale production. This study aimed to evaluate the development of natural nodulation, the associated characters and the processing of roots progenies from different Brazilian regions, kept in the Germplasm Bank of the National Institute of Amazonian Research-INPA, in Manaus. The experiment was conducted on Red Yellow Argisol in Horticulture Experimental Station Alejo Von der Pahlen, the National Institute of Amazonian Research-INPA, located at km 14 of the AM-010 highway, city of Manaus, AM, from January to July 2014. We adopted the experimental design of randomized blocks, with 64 treatments (the yam bean progenies) with five replicates (five competitive plants). The biomass variables of fresh shoots, and shoot dry, stem, leaves, roots, nodules, and total biomass, number of nodes, specific weight of nodules, relating to development and natural nodulation were evaluated when 50% of plants reached the flowering stage, at 100 days after transplantation. The magnitude of genetic differences were used the following characters: plant height, number of secondary branches, biomass fresh shoot, stem diameter, biomass tuberous root, number of roots, width of the tuberous root, root length tuberose, length width ratio of tuberous root and form of the tuberous root. The processing of the roots was carried out with 86 kg of roots of bean-macuco in family farmer flour home in Iporá-AM settlement, adopting the same cassava flour production technique practiced by traditional farmers of the Amazon. About quantitative data proceeded to analysis of variance by F test, mean comparison by Duncan test, estimates of phenotypic, genotypic and environment, cluster analysis using as dissimilarity measures the generalized Mahalanobis distances (d²). It was found that 98.4% of yam bean progenies nodulated naturally with indigenous rhizobia. The progenies P6, P10, P11 and P13 stood out in dry total biomass and the number of nodes established naturally in their root systems. In productivity components number and mass of roots, the progenies that stood out were the P52 with 4.53 roots and the P22, with mass of 5.38 kg of roots per plant. The genotypic correlations generally were higher than the phenotypic and environmental, showing greater contribution of genetic factors on the expression of these traits in relation to other correlations. Since the genetic correlations involve a combination of inheritable nature, may be used in future yam bean breeding programs for the State of Amazonas. 86 kg of bean-macuco fresh root yield, after processing, adopting the same technology used in the production of cassava flour was achieved by a 8.6 kg of starch yield, 7 kg of flour, 16 kg of bark and 54.31 kg of waste liquid. Starch generated from the raw roots have slow settling process similar to arrowroot starch. In general, the 64 studied yam bean progenies showed several characteristics of agronomic importance for immediate use by farmers of Amazonas state, and future studies for the genetic improvement of this species.
Keywords: Raízes de feijão; Feijão-macuco; Fabaceae